EMPLOYEES’ MOTIVATIONAL FACTORS DURING THE ENDEMIC PHASE - Azmiah Abdul Razak; Nurisyal Muhamad (International Journal of Accounting, Finance and Business, 2022)
COVID-19 outbreaks had somehow changed the employees' routine and activities, consequently influencing their work motivation. Even in the endemic phase, the employees need to adapt to changes that might further impact their job performance. Thus this study aims to identify the key motivational factors that can lead to job performance in the current context. This article provides a theoretical model that suggests the main elements that could influence job performance during the endemic phase, such as training, home office environment, remuneration, teamwork, and connection facilities. The model suggested is suitable to be the guideline for the management to enhance job performance during the endemic stage.